Bilingualizing linguistically homogeneous classrooms in Kenya: implications on policy, second language learning, and literacy - Mose, Peter Nyakundi (International journal of bilingual education and bilingualism, 2019)
Bilingualism characterizes people in linguistically heterogeneous settlements like Nairobi among other urban centres in Kenya. But the country is also predominantly rural (where you find people of a common language settled in one geographical rural region) in which mother tongues are primary means of communication. Children in lower primary in rural areas should be taught in their mother tongues. The purpose of this study was to find out the use of mother tongues and official languages in elementary linguistically homogeneous classrooms in Kenya and the possible effect of this use. Data were obtained through classroom observations and interviews with classroom teachers and head teachers. The findings indicate that instead of using mother tongues to teach, teachers use Kiswahili (a national and co-official language) and English (an official language) in various ways to teach content subjects; mathematics, science, social/religious studies, hence making the classrooms bilingual. The article presents evidence and discusses how this use of language affects learning and what it implies on language in education policy, on second language learning, and on early literacy development. Negative effects of the practice include poor learning outcomes and poor teacher morale. The study recommends corrective steps to avert learning and literacy development losses.